Development of ESD - Oriented Google Sites Learning Media to Improve Critical Thinking Skills of Elementary School Students - Damayanti, Rika; Suratmi, Suratmi; Raharjo, Makmum (LPPM STKIP Kusuma Negara, 2025)
This study aims to develop a product in the form of ESD-oriented Google Sites learning media to improve critical thinking skills of grade IV students of SDN 05 Indralaya. The type of research used in this study is development with the ADDIE model. The subjects used in this study were class IV A of SDN 05 Indralaya. Data collection techniques used were interviews, questionnaires, tests, observations and documentation. The results of the validation of material experts obtained a percentage of 98.21% with a very feasible category. The validation of media experts obtained a percentage of 90.38% with a very feasible category. The validation of practitioner experts obtained a percentage of 99.07% with a very feasible category. The results of student responses at the individual stage obtained a percentage of 96.53% with a very practical category and at the small group stage obtained a percentage of 97.22% with a very practical category. The N-Gain score obtained was 0.855 with a very high category, thus it can be concluded that the resulting product is feasible to use in learning activities.